Safety of outpatient non-upper airway surgery for patients with obstructive sleep apnea in ambulatory surgical centers: A systematic review. - Muaaz Asghar; Kenny Pang; Mauz Asghar; Brian Rotenberg (PLoS ONE, 2025)
Objective The systematic review aims to determine the safety of conducting non-upper airway surgery in an ambulatory surgery center (ASC) for OSA patients. Data sources A comprehensive search was conducted from MEDLINE, Embase, CENTRAL, and Scopus from inception through February 2023. Review methods Studies including non-upper airway surgery done in ASC settings were identified. Risk of bias was assessed using the Murad Tool and Newcastle-Ottawa scale. Primary outcomes were 24 hour complications and unplanned admission rates. Results From 9313 studies, 13 non-OSA studies with 31,200 OSA participants and 318,709 non-OSA participants were identified. Severe complications were rare and tended to occur within the first 4 hours of the postoperative period. While a majority of smaller scale studies found no significant difference in unplanned admissions, large scale studies with multivariate analysis find OSA to be an independent risk factor for unplanned admission and 30-day complications. However, large scale ASC studies have found that with proper selection and perioperative interventions, OSA patients can undergo outpatient surgery at ASCs safely. Conclusions OSA patients with mild or controlled comorbidities can safely undergo ambulatory non-OSA surgery in ASCs. Other The protocol for this review was registered with the PROSPERO database (Registration number: CRD42023415162).